Analysis of Loyok Village’s Strategies in Building Community-Based Tourism Resilience - Hilmiyatun; Ahmad Ramdani; Anggun Octaviani; M. Yusran Azani; Ainiawati (Language Assistance, 2025)
This research aims to analyze how the community of Loyok Village builds tourism resilience through community-based practices in the aftermath of the 2018 Lombok earthquake and the COVID-19 pandemic. The study employs a qualitative descriptive approach, with the research site located in Loyok Village, Sikur District, which is known as a bamboo-craft tourism village. Informants were selected purposively and included village government officials, BUMDes managers, Pokdarwis members, bamboo artisans, MSME actors, and community beneficiaries. Data were collected through in-depth interviews, participant observation, and document analysis, and were then examined using thematic analysis. The findings indicate that tourism resilience in Loyok is constructed through several key strategies. First, strengthening local institutional capacity by clarifying the roles of the village government, Pokdarwis, BUMDes, and artisan groups, as well as expanding networks with external stakeholders. Second, developing a diversified BUMDes business model that functions as an economic intermediary for local residents. Third, product innovation and the digitalization of bamboo-craft marketing serve as adaptive strategies for artisans in response to declining tourist visits. Fourth, Pokdarwis plays a crucial role in ensuring the continuity of tourism activities and improving service quality. Fifth, social capital in the form of mutual cooperation and community solidarity constitutes an essential foundation for economic and tourism recovery.These findings underscore that community-based tourism resilience in Loyok Village does not rely solely on formal policies, but is also shaped by the strength of local institutions, economic creativity, and the social cohesion of the community.